Developing strategies to commercialise biofortified crops and foods - Nyangaresi, Annette M.; Friesen, Valerie M.; McClafferty, Bonnie; van der Merwe, Charl; Haswell, Daniel; Reyes, Byron; Mudyahoto, Bho; Mbuya, Mduduzi N. N. (Global Alliance for Improved Nutrition, 2022)
Biofortification (or nutrient enrichment) of staple crops has the potential to contribute to reducing micronutrient deficiencies by increasing micronutrient intakes. In 2019, GAIN and HarvestPlus entered a partnership to lead the Commercialisation of Biofortified Crops (CBC) Programme, which aims to catalyse commercial markets for biofortified crops in six countries across Africa and Asia. During the CBC programme inception phase, information on the value chains and their challenges and opportunities for commercialisation were collected for each country-crop combination through literature reviews and third party-led commercialisation assessments. In this paper, we summarise the processes undertaken to identify the potential opportunities and barriers for commercialisation and describe how the findings were used to develop commercialisation strategies for nine country-crop combinations.